Usability Testing Analysis of Bank Aceh Mobile Action Applications Using Human Centered Design and Heuristic Evaluation Methods - Amalia, Fatihah Indah; Fitria, Rahma; Ulva, Ananda Faridhatul (Journal of Artificial Intelligence and Software Engineering, 2025)
One of the efforts to improve regional digital banking services is through the development of Bank Aceh Syariah's Action Mobile application. This application is designed to facilitate customers in conducting various transactions online, such as transfers, payments, and mutation checks. However, despite being available on the Google Play Store and receiving favorable ratings, the usage of this application is still relatively low compared to other regional banks' mobile banking applications. Some of the problems found are related to user experience, including limited e-commerce payment features and digital wallet top-up services that only support certain platforms such as OVO, GoPay, and LinkAja. In addition, the information displayed in the transaction mutation section is also considered incomplete, resulting in complaints from users. This problem has the potential to hinder comfort in using the application and affect the level of customer satisfaction. To overcome these challenges, an evaluation of the application's usability was conducted using the Human Centered Design approach and the Heuristic Evaluation method. The evaluation involved users and experts who provided feedback based on Nielsen's ten heuristic principles. The results showed some weaknesses in the application design, such as navigation that was not fully intuitive, information delivery that was not clear, and inadequate service features. Based on these findings, a solution was designed in the form of a new application prototype that was more responsive and user-friendly. The design was carried out using the Figma application, focusing on improving the interface and adding the required features. With these improvements, it is expected that Action Mobile Bank Aceh Syariah can be more competitive in the midst of the rapid development of digital banking services. This technology is also part of a strategic step in supporting digital banking transformation in the region, as well as increasing customer satisfaction and loyalty.